Evaluation of the Swedish Interactive Thresholding Algorithm, a new thresholding algorithm, of the Humphrey field analyzer in normal subjects - Tsuji, A; Inazumi, K; Yamamoto, T; Kitazawa, Y (Nippon Ganka Gakkai zasshi, 1998)
The Swedish Interactive Thresholding Algorithm (SITA) is a new thresholding algorithm that aims to obtain the same quality of visual fields in a shorter examination time than with the conventional up-and-down method. We investigated the correlation between thresholds measured with the SITA algorithm and those with the conventional up-and-down method in 47 eyes of 47 normal subjects. In each test point, thresholds with the SITA accurate and with the SITA fast showed significant correlation with those of the conventional method (r = 0.693, p < 0.0001 and r = 0.689, p < 0.0001, respectively). The mean deviation (MD) in the conventional method and the difference between MD values of the conventional method and SITA accurate and SITA fast were significantly correlated (r = -0.442, p < 0.006 and r = -0.509, p < 0.00092, respectively). The examination times of the SITA accurate and SITA fast were 48% and 27% of the conventional method. Although the new thresholding algorithm enables us to perform perimetric examination with relatively high accuracy, further investigations should be conducted before we apply it to glaucoma cases.